Envy, Social Comparison, and Depression on Social Networking Sites: A Systematic Review - Fabio Carraturo; Tiziana Di Perna; Viviana Giannicola; Marco Alfonso Nacchia; Marco Pepe; Benedetta Muzii; Mario Bottone; Raffaele Sperandeo; Vincenzo Bochicchio; Nelson Mauro Maldonato; Cristiano Scandurra (MDPI AG, 2023)
This study aims to review the evidence for the reciprocal relationship between envy and social comparison (SC) on social networking sites (SNSs) and depression. We searched PsychINFO, PubMed, and Web of Science from January 2012 to November 2022, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A total of 9 articles met our inclusion criteria. In all articles reviewed, a simple correlation was found between SC on SNSs, envy, and depression. Three cross-sectional studies successfully tested a model with envy as a mediator between SNSs and depression. The moderating role of additional variables such as self-efficacy, neuroticism, SC orientation, marital quality, and friendship type was also evident. The only two studies that were suitable to determine direction found that depression acted as a predictor rather than an outcome of SC and envy, and therefore depression might be a relevant risk factor for the negative emotional consequences of SNSs use.